Exploring the Revitalization School School-Level Geography Education in Nepal - Dhakal, Keshav Raj (The Third Pole: Journal of Geography Education, 2025)
This study explores the revitalization of school-level geography education in Nepal. Revitalization in school-level geography education is a strategy to improve the relevance, engagement, and effectiveness of geography education in addressing contemporary challenges. Geography education in secondary schools in Nepal plays an important role in promoting spatial understanding and reasoning. However, it remains marginalized within the secondary level, due to lack of dedicated discipline status, modern teaching methods, and institutional support. This study employs a qualitative document analysis to examine the current status, challenges, and opportunities for reform in secondary-level geography education. Major issues include outdated curricula and textbooks, insufficient teacher training, limited utilization of geospatial technologies, and evaluation techniques. The paper presents strategic directions for strengthening the geography education, including curriculum and textbooks reform, teacher professional development, integration of geospatial technologies, field-based and experiential learning, improved assessment methods, and enhanced education policy. The findings also highlight the need for a national strategy that strengthens geography education at the school level to meet demands and support national priorities.